PENGARUH KOMITMEN ORGANISASIONAL TERHADAP KEPUASAN KERJA KARYAWAN CV KARYA TARUNA TEKNIK - Riyanti Teresa; Benedicta Evienia P (Prosiding Working Papers Series In Management, 2017)
This research was conducted to find out whether organizational commitment variables such as: affective commitment, continuance commitment, and normative commitment have significant influence either partially or simultaneously to the job satisfaction of employees of the CV Karya Taruna Teknik. Data collection method using primary data and secondary data method. Primary data were collected, which is distributing questionnaires to 50 permanent employees of CV Karya Taruna Teknik. While the secondary data required obtained from web and internet. The research analysis was done by using multiple linear regression analysis. Data procrssing research using SPSS 23 for Windows. The result of hypothesis test shows that the affective commitment not have a significant influence on job satisfaction partially but affective commitment, continuance commitment, and normative commitment have a significant influence on job satisfaction simultaneously . Continuance commitment is found as the factor that has the most powerful influence on job satisfaction.Keywords: Employee Satisfaction, Organizational Commitment